The Effect of Prenatal Gentle Yoga on the Anxiety Level Among Pregnant Women Trimester III in Facing Childbirth Phase - Irmasanti Fajrin; Wahyuni Wahyuni (Jurnal Ilmiah Kesehatan (JIKA), 2023)
Anxiety and depression in pregnancy are disorders and are the second biggest cause of disease in 2020. Pregnancies with high levels of anxiety will affect the outcome of fetal neurological development which is related to cognitive, emotional, and behavioral development until childhood. This research aims to identify the effect of prenatal gentle yoga on the anxiety level of pregnant women in the third trimester when facing childbirth at the Sifra Independent Practicing Midwife. This research uses a quasi-experimental research design with a control group pre-post test design. The experimental group's samples were 20 subjects, and the control group was 20 subjects. Purposive sampling technique. The results showed the experimental group’s average anxiety score before and after intervention with a p-value=0,000 (p-value<0,05). This shows that there is a significant difference in the average anxiety score before and after being given prenatal gentle yoga intervention. The results of the study using the Independent-Sample T-Test showed that the average anxiety score after intervention in the experimental group was 8,35, while the average anxiety score after intervention in the control group was 23,05 with a mean difference of -14,700 and a p-value =0,000 (p-value<0,05), shows a significant difference in the mean anxiety score after the intervention between the experimental group and the control group. The conclusion of the research is that prenatal gentle yoga has an effect on the anxiety level of pregnant women in the third trimester when facing childbirth.